The Role of the 'Post Graduate Diploma in Secondary School Teaching' Program in Improving the Quality of Teaching in Eastern Ethiopian Secondary Schools - Sisay Wondemetegegn; Anwar Ahmed; Tamrat Zelalem (Ignatianum University Press, 2017)
This study dealt with the role of the Postgraduate Diploma in Secondary School Teaching (PGDT) program in improving the quality of teaching in Eastern Ethiopian secondary schools. The study used a mixed research design that integrated both qualitative and quantitative research methods concurrently. The data was collected from 140 respondents, comprised of 83 teachers and 57 school leaders (i.e., mentors, principals, and head teachers) of 14 secondary schools found in four zones of Eastern Ethiopia. The researchers used simple random sampling to select secondary schools, whereas teachers and school leaders were selected using purposive and expert sampling techniques respectively. Quantitative data was collected via a questionnaire and qualitative data through focus group discussion (FGD), interview, and observation. The data is analyzed both in a qualitative and a quantitative manner. The findings of the study showed that PGDT graduates seem to be contributing their part to enhancing quality education by raising high order thinking questions, implementing classroom activities such as: problem-solving, cooperative leaning, discussion and brainstorming, ^L1/2016 (9) Multidisciplinary Journal of School Education Sisay Awgichew Wondemetegegn Anwar Ahmed Tamrat Zelalem 166 frequently managing the classroom for active learning implementation, using exercises to elicit students' ideas, knowledge and skills and encouraging students to become active participants in classrooms. This is considered to be an encouraging trend for the desired improvement in teaching quality. The result of this study also demonstrated that PGDT graduates have good subject matter knowledge and apply it effectively in their classrooms. The grand mean of teachers' and school leaders' responses related with their subject matter knowledge is 4.33 and 3.81, respectively. This seemed to exist because of their undergraduate program; they have had an opportunity to attain various major courses in the three-year bachelor program. After that, in order to become a high school teacher, they had to attend a one-year or a two-summer long PGDT program to equip them with fundamental pedagogical skills. This is understood as the benefit of the new teacher-education program. Despite all of these facts and in contrast with the teachers' response, the researchers observed that in most Eastern Ethiopia secondary schools teaching was dominated by traditional methods of teaching or lecturing. This approach makes students passive, less confident, unreflective and poorly motivated to enjoy learning. Furthermore, concerning students learning assessment, an inconsistency of application was observed. Therefore, the researchers suggested that the Ethiopian Ministry of Education, in collaboration with higher learning institutions and teacher-training colleges, would have to provide continuous training for secondary school teachers about student assessment, active and constructivist methods of teaching to enhance quality education and produce robust graduates fit for the 21st century world of work and consciousness. Keywords: quality, teaching, PGDT